Supportive Intervention Challenges for Patients with Breast Cancer: A Systematic Review - Zaker, Mohammad Reza; Safaripour, Amin; Rahdaneh Zade Sabegh, Sima; Barjasteh, Samira (Asian Pacific Journal of Environment and Cancer, 2022)
Background: Cancer and its treatment can have a profound effect on the appearance of the patient, the aim of this systematic review was to identify challenges among patients with breast cancer and the effective intervention for coping it. Materials and Methods: This systematic review that was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines between January 2000 to December 2018. The keywords searched included: “breast cancer,” “breast neoplasm,” “breast tumor,” “educational intervention,” “cognitive program,” “body image,” “supportive intervention,” “family,” “behavioral therapy,” “counselling,” “husband,” and “spouse,”. The Google Scholar, ISI Web of Science, Science Direct, PubMed and Scopus databases were searched. Results: After screening and review of article eligibility, ten were included in the study. The selected articles were compared regarding the aims of interest. The results showed some effective factor in the improvement of patients with breast cancer including family support, supportive programs, physically and psychologically support with family and relatives, holistic care, psychological screening and consultation, social support, family involvement in the treatment process of women with breast cancer. Conclusion: According to the results, the most problem of all articles was body image and the best effective way is family support.